ประสบการณ์ความงอกงามหลังการเข้ากลุ่มการปรึกษาเชิงจิตวิทยาของนิสิตนักศึกษาที่มาจากครอบครัวหย่าร้าง : การศึกษาเชิงคุณภาพแบบทีมวิจัยเห็นชอบร่วมกัน - สมรักษ์ ทองทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This Consensual Qualitative Research was conducted to study the growth experience of university students who came from divorced family after participated in group counseling. Eleven Bachelor’s Degree students who participated in group counseling for students from divorced family at an university counseling center were in-depth interviewed. The consensus qualitative data analysis identified the growth experiences as a positive change in 11 domains from all informants which are increasing openness to themselves, having a good relationship with other members in the group, having a good relationship with family members, having a good relationship with others, having an inspiration from stories of members and experiences within the group counseling, having positive perception toward obstacles, growth in trace after divorce, being more self-awareness, being more peacefulness, being more self – congruence and more understanding of the truth of life. Divorce in family is called as a stress and painful event in life, nevertheless, the growth experience according to the self-report shows some growth related to their experience in the group counseling and some growth related to their learning as being grow up from divorced family. At the end, research findings were discussed and some suggestions for further study were proposed.